2021
DOI: 10.1029/2021gl095704
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Foreshocks Indicating Cascading Rupture Developments for 527 M 0.9 to 5.4 Ridgecrest Earthquakes

Abstract: Identifying and observing geophysical signals of slip events preceding earthquakes have been of paramount importance because of their direct linkage with earthquake nucleation and rupture processes (e.g., Bou-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 91 publications
1
15
0
Order By: Relevance
“…Near‐field observations with bore‐hole strain meter have reported no similar nucleation signals so far (Roeloffs, 2006), even before the 2004 Parkfield earthquake (Johnston et al., 2006). Meng and Fan (2021) detects immediate foreshocks in the 2019 Ridgecrest aftershocks, but found that they follow mostly the cascade mode, with no scaling between the characteristic of their P wave and the magnitude of target event. Though Tape et al.…”
Section: Resultsmentioning
confidence: 99%
“…Near‐field observations with bore‐hole strain meter have reported no similar nucleation signals so far (Roeloffs, 2006), even before the 2004 Parkfield earthquake (Johnston et al., 2006). Meng and Fan (2021) detects immediate foreshocks in the 2019 Ridgecrest aftershocks, but found that they follow mostly the cascade mode, with no scaling between the characteristic of their P wave and the magnitude of target event. Though Tape et al.…”
Section: Resultsmentioning
confidence: 99%
“…Extending these ideas 12 , we suggest that faults that are more strongly velocity weakening and/or those with significant overstress may host fast creep fronts that can quickly accelerate into subsequent dynamic rupture and may only be identified seismically as a 1-10 s pause between a triggering event and its (potentially larger) aftershock 63,64 . Faults that are strongly velocity strengthening will produce creep fronts with more limited spatial extent 8 , where asperities act in isolation and are less likely to trigger neighboring earthquakes on days-to-years timescales 4 .…”
Section: Discussionmentioning
confidence: 76%
“…In real fault systems, the cascade and preslip models of nucleation are not mutually exclusive and indeed may feedback on one another (Cattania & Segall, 2021; McLaskey, 2019; Noda et al., 2013). Recent observations from high‐resolution earthquake catalogs around the world (Cabrera et al., 2022; Durand et al., 2020; Ellsworth & Bulut, 2018; Feng et al., 2021; Gardonio et al., 2020; Malin et al., 2018; H. Meng & Fan, 2021; Moutote et al., 2021; Sánchez‐Reyes et al., 2021; Shelly, 2020; Trugman & Ross, 2019; M. P. A. van den Ende & Ampuero, 2020; Yao et al., 2020; Yoon et al., 2019) are beginning to bridge the gap between laboratory and field scales by providing more complete and holistic observations of the nucleation process. The diverse range of physical processes highlighted by these recent studies suggest that earthquake nucleation does not follow a simple, uniform trajectory common to all earthquakes, but instead may be complex and highly dependent on the details of the faulting environment and stress regime.…”
Section: Science Enabled By Big Data Seismologymentioning
confidence: 99%